2014
DOI: 10.1039/c4ob01152j
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazole–oxadiazole conjugates: synthesis, antiproliferative activity and inhibition of tubulin polymerization

Abstract: A number of pyrazole-oxadiazole conjugates were synthesized and evaluated for their ability to function as antiproliferative agents on various human cancer cell lines. These conjugates are comprised of pyrazole and oxadiazole scaffolds closely attached to each other without any spacer as two structural classes. The Type I class has a trimethoxy substituent and the type II class has a 3,4-(methylenedioxy) substituent on their A rings. Among these conjugates 11a, 11d and 11f manifest potent cytotoxicity with IC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 35 publications
(50 reference statements)
0
24
0
Order By: Relevance
“…These were oxidized to the pyrazole carbaldehydes (11a-d) by using IBX in DMSO. 24 These pyrazole carbaldehydes upon reaction with (carbethoxymethylene)triphenylphosphine, Ph 3 PCHCO 2 C 2 H 5 (C2-Wittig salt) in toluene afforded α,β-unsaturated esters 12a-d that subsequently underwent a base hydrolysis to give α,β-unsaturated carboxylic acids 13a-d. 26,27 Finally, these carboxylic acids conveniently coupled with substituted arylamines 14a-d in the presence of EDC/ Hobt produce the desired pyrazole linked phenylcinnamides (PP). 19 By employing the same methodology isoxazole linked (1), combretastatin-A4 (2), nocodazole (3), phenylcinnamides (4), thiadiazole ring based cinnamide (5), acrylylpiperazine (6) phenylcinnamide conjugates 21a-n were synthesized starting from isoxazole esters (16a-d) as shown in Scheme 2.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…These were oxidized to the pyrazole carbaldehydes (11a-d) by using IBX in DMSO. 24 These pyrazole carbaldehydes upon reaction with (carbethoxymethylene)triphenylphosphine, Ph 3 PCHCO 2 C 2 H 5 (C2-Wittig salt) in toluene afforded α,β-unsaturated esters 12a-d that subsequently underwent a base hydrolysis to give α,β-unsaturated carboxylic acids 13a-d. 26,27 Finally, these carboxylic acids conveniently coupled with substituted arylamines 14a-d in the presence of EDC/ Hobt produce the desired pyrazole linked phenylcinnamides (PP). 19 By employing the same methodology isoxazole linked (1), combretastatin-A4 (2), nocodazole (3), phenylcinnamides (4), thiadiazole ring based cinnamide (5), acrylylpiperazine (6) phenylcinnamide conjugates 21a-n were synthesized starting from isoxazole esters (16a-d) as shown in Scheme 2.…”
Section: Chemistrymentioning
confidence: 99%
“…[21][22][23] Previously we have reported that a series of pyrazole based conjugates have shown profound cytotoxic effects by arresting the cells in the G2/M phase. [24][25][26] In view of the attractive biological activities exhibited by them, considerable interest in the development of newer cytotoxic agents has been aroused. The present work illustrates the design and synthesis of some pyrazole/isoxazole linked arylcinnamide conjugates and evaluates their ability to inhibit the growth of a panel of four human cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Silica gel 60 A mixture of aldehyde I (1.0 mmol), 4-phenylurazole (1.0 mmol) and ethyl/methyl acetoacetate II (1.0 mmol), 3 mL of [bmim]BF 4 , and L-proline (10 mol%) was placed in a 50-mLround-bottomed flask. The reaction contents were stirred magnetically in an oil bath maintained at 80°C for appropriate time as mentioned in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…triazole-6-carboxylate (IIIa) [17] 4 . Operational simplicity, lesser reaction time, high yields of products, and recyclability of catalyst and ionic liquids are the conspicuous advantages of the present protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation